ANALYSIS OF GLARE INDEX AND INDOOR SURFACE LUMINANCE WITH KINETIC FACADE USING HIGH DYNAMIC RANGE (HDR) IMAGE - Fatasya, Sherlyna
A kinetic facade is a facade that can move or adapt in response to environmental factors, such as sunlight. In its application, this facade has the potential to optimize the use of natural light in buildings by regulating the amount of light entering the interior. When utilizing natural light, it is essential to consider its impact on the visual comfort of users. Visual comfort can be represented by the glare index, which is evaluated, among other factors, based on surface luminance within the space. The glare index and surface luminance can be determined through High Dynamic Range (HDR) image analysis. This study analyzes indoor visual comfort with a kinetic facade featuring a tensile fabric structure (KBKT). The analysis was conducted under conditions aligned with optimal facade opening scenarios based on variations in sky diffuse irradiance. However, since the analysis was carried out computationally, model validation was first performed using a prototype measured in an artificial sky room of the mirror type. Based on the model validation, the simulation model was found to be sufficiently accurate, with an error value of less than 12%, but only within a specific simulation time range, namely between 9:00 AM and 2:00 PM. Referring to these validation results, further simulations were conducted to evaluate the visual comfort of spaces with the KBKT facade using point-in-time analysis across 4 different days and 2 time conditions. The evaluation utilized the DGP glare index to determine the glare level in the room model, along with false-color surface luminance mapping, and DGPs values analyzed based on vertical illuminance within the space.The simulation results showed that in almost all simulated time scenarios, the glare was categorized as imperceptible, except on June 21 at 11:00 AM, when it fell into the perceptible glare category. Based on the DGPs heatmap results, it was found that almost all simulated scenarios indicated that spaces with the KBKT facade produced 100% imperceptible glare zones, except for one condition, which produced a value of 96,25%.